Diurnal variation in serum cortisol concentrations in asthmatic subjects after allergen inhalation. - Durham,SR; Keenan,J; Cookson,WO; Craddock,CF; Benson,MK (Thorax, 1989)
To assess whether differences in the adrenal response to allergen are important in determining the magnitude of the allergen induced late responses in asthmatic subjects, we measured serum cortisol concentrations after inhalation challenge with allergen or control solution (phosphate buffered saline). The two challenges were performed in random order with an interval of 14 days. A normal diurnal decrease in serum cortisol concentrations was observed on both days. Mean blood cortisol concentrations three hours after inhalation of allergen (before the late response), nine hours afterwards (at the time of the late response), and 24 hours afterwards were virtually identical to those observed after inhalation of phosphate buffered saline. Serum cortisol concentrations before challenge and three, nine, and 24 hours after challenge were not related to the diurnal increase in blood eosinophils on the control day, or to the size of the late asthmatic response or accompanying changes in blood eosinophils after allergen challenge. It is concluded that serum cortisol concentrations show normal diurnal variation after allergen challenge and are unrelated to the size of the late response or associated changes in blood eosinophil counts.